Fatores clínicos e sociodemográficos associados ao tratamento do tumor de wilms: experiência do INCA - Gutierrez, Francisca Norma Albuquerque Girão (2013)
Wilms tumor is the most common renal tumor in childhood. There are few publications related to the time to diagnosis specifically on this tumor histology. Objective: To analyze cases of unilateral Wilms' tumor diagnosed and treated in a single institution, describing its demographic, social, clinical, disease characteristics and care and to correlate with the different time components of diagnosis and treatment of patients. Patients and methods: We retrospectively analyzed 98 patients admitted from 2003 to 2012, who received treatment according to SIOP 2001 nephroblastoma protocol. Data collection was performed from patients' medical records. Variables analyzed included demographic, socioeconomic, clinical, tumor-related and treatment care. Time to diagnosis were evaluated: family, medical referral, from beginning of symptoms to INCA admission and from admission to the beginning of treatment. Results: Median age at diagnosis was 3 years (range: 4 m to 15 years), M/F: 1,2/1, 58 cases (59.2%) from the State of Rio de Janeiro. The median maternal age was 27 years. In 48/98 (71.6%) mothers it was evidenced elementary education complete or incomplete. The presence of a mass in the abdomen, as the main complaint, occurred in 53/98 (54.1%) cases and was identified by the mother in 90.6% of cases and by the pediatrician in 5 cases. Localized disease was observed in 82/98 (83.7%) patients and metastatic disease in 16/98 (16.3%) cases. The median tumor volume in localized disease at diagnosis was 503 cm3 and in metastatic disease was 865.0 cm3 (p <0.05). In 58/72 (80.5%) cases with medical record information, the medical diagnosis suspicion was made at the emergency room. Age greater than two years old and metastatic disease at diagnosis were related to familiar time delay, origin distant to large urban centers was related to delay in referral time. Conclusion: Educational programs for early diagnosis and establishment of a referral chain for specialist treatment are essential for reducing the time to diagnosis and provide effective treatment.